Immunoprofiling of Rice Root Cortex Reveals Two Cortical Subdomains - Henry, Sophia; Divol, Fanchon; Bettembourg, Mathilde; Bureau, Charlotte; Guiderdoni, Emmanuel; Périn, Christophe; Diévart, Anne (Frontiers in Plant Science, 2016)
The formation and differentiation of aerenchyma, i.e., air-containing cavities that are critical for flooding tolerance, take place exclusively in the cortex. The understanding of development and differentiation of the cortex is thus an important issue; however, studies on this tissue are limited, partly because of the lack of available molecular tools. We screened a commercially available library of cell wall antibodies to identify markers of cortical tissue in rice roots. Out of the 174 antibodies screened, eight were cortex-specific. Our analysis revealed that two types of cortical tissues are present in rice root seedlings. We named these cell layers 'inner' and 'outer' based on their location relative to the stele. We then used the antibodies to clarify cell identity in lateral roots. Without these markers, previous studies could not distinguish between the cortex and sclerenchyma in small lateral roots. By immunostaining lateral root sections, we showed that the internal ground tissue in small lateral roots has outer cortical identity.